Severe Insulin Resistance Improves Immediately After Sleeve Gastrectomy - Rahul Sharma MD; Chandra Hassan MD; Joumana T. Chaiban MD (SAGE Publishing, 2016)
Introduction . Obese individuals exhibit insulin resistance often leading to adverse health outcomes. When compared with intensive medical therapy, bariatric surgery has shown better outcomes mainly in terms of insulin resistance and glycemic control. Using the Homeostasis Model Assessment of insulin resistance (HOMA-IR), we report herein a case illustrating a drastic improvement in severe insulin resistance after sleeve gastrectomy in the immediate postoperative period. Case Report . A patient with long-standing history of morbid obesity, type 2 diabetes, obstructive sleep apnea, hypertension, and severe insulin resistance (requiring approximately 2 units of insulin per kg per day) was enrolled in the medical weight management program for 6 months during which he lost 40 lbs and his insulin requirements decreased. He then underwent a sleeve gastrectomy and did not require insulin therapy as of postoperative day 1. His HOMA-IR improved by about 76% between day 1 and day 14 postoperatively. Conclusion . Sleeve gastrectomy leads to a drastic improvement in severe insulin resistance as early as the first postoperative day.